Die Partikeln schon und noch in der linearen Abfolge mit Temporaladverbien - Anna Kutscher (Linguistik Online, 2019)
The particles schon and noch in German add an aspectual reading to events in different assertions. While schon tends to a perfective reading of an event, an imperfective reading appears with noch, hence both particles have a similar function on the event modification. Overtly, they are located unrestricted in the middle field of a German clause and can freely change their position towards temporal adverbs such as heute, jetzt, bald etc. It seems that syntax does not have an impact to order schon heute or heute schon. This variation is of main interest of the paper: Is there a linear restriction of adverbs and schon/noch, and does a change in the output cause a reinterpretation? The paper presents main assumptions on the word order of aspectual particles and temporal adverbs from the semantic and the syntactic perspective. An experimental study on prosodic factors will complete the overview and its preferences for the linearization of the sequences in question. The result is that common categorical grammar is not able to account for all possible outcomes with respect to contextual preferences. Therefore, a more flexible grammar concept is needed to build a usage-based concept on word order variation for these functional elements.